Diagnosa Kerusakan Motor Honda Sport Non Injeksi Metode Certainty Factor - Eka Yuandi, Rizky; Winardi, Slamet (Jurnal Etnik: Ekonomi-Teknik, 2023)
Users of Honda motorbikes have been increasingly popular for many years, ranging from young people to adults. In general, motorbike users do not understand the damage that occurs to motorbikes and tend to hand it over to technicians without knowing whether the damage is simple or complicated to repair. With these considerations, it is necessary to make a system of tools to detect damage that occurs to motorbikes, so we need a system that can help motorbike users to overcome problems of damage that occurs to motorcycles, especially Honda Sport GL Pro, Megapro, and Tiger. A knowledge-based system for identifying motorcycle damage that is displayed using a web-based programming language. forming a decision tree and used to classify the damage into damage that most affects the motor to minor damage. Complaints are generated so that a system can be created that can help users for initial handling that occurs on motorbikes and is expected to speed up the repair of motorbikes that are classified as mild damage.